2018
DOI: 10.1111/aas.13149
|View full text |Cite|
|
Sign up to set email alerts
|

Publications by Scandinavian university Departments of Anaesthesiology from 2001 to 2015

Abstract: The number of publications from Scandinavian university Departments of Anaesthesiology increased between 2001 and 2015, but the share of original articles decreased. Copenhagen was the most productive university Department of Anaesthesiology based on the number of publications and citations of original articles. Finnish university Departments of Anaesthesiology led in the share of original articles out of all publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Moreover, we showed that the number of publications from global anesthesia departments had a steady trend before 2004, but had an average annual growth rate that increased from 2.02 to 5.53% after 2004 ( Figure 2 ). These findings were similar to former bibliometric studies of clinical research from anesthesia departments of G-20 countries ( 19 ), European countries ( 20 , 21 ), and Scandinavian countries ( 22 ). Together with the subject-field's trend, the widening gap of publications between the two datasets was unveiled.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, we showed that the number of publications from global anesthesia departments had a steady trend before 2004, but had an average annual growth rate that increased from 2.02 to 5.53% after 2004 ( Figure 2 ). These findings were similar to former bibliometric studies of clinical research from anesthesia departments of G-20 countries ( 19 ), European countries ( 20 , 21 ), and Scandinavian countries ( 22 ). Together with the subject-field's trend, the widening gap of publications between the two datasets was unveiled.…”
Section: Discussionsupporting
confidence: 90%
“…Research activity of anesthesiology includes both clinical and basic studies. Distinct from the aforementioned studies on anesthesiology conducted on a subject-field basis, there were a few bibliometric studies on global clinical trials ( 18 ), as well as publication of clinical research from the G-20 countries ( 19 ), the European countries ( 20 , 21 ), Scandinavian countries ( 22 ), Canada ( 23 ), and East Asia ( 24 ), based on authors' affiliated departments. It is important to also inspect comprehensive department-based data, including all clinical and basic studies, in order to more thoroughly understand the overall condition of publications dealing with anesthesiology.…”
Section: Introductionmentioning
confidence: 99%
“…16 In the absence of numerous denominators, data have to be normalized as best as possible. 10,17 Normalization also takes into account that it is not possible to accurately capture the resources available to countries or institutions such as funding, infrastructure, legal requirements, or workforce. 17 It is therefore more useful to look at positions within a group or at trends based on previous numbers for a given unit.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also have limited validity, for example, due to a large temporal bias. 10 Since the quality of citations cannot be measured, the number of citations does not necessarily indicate the value of the research. The h-index incorporates bias from citation counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation